Co-administration of herbal inhibitors of P-glycoprotein with renal drugs enhance their bioavailability- In silico approach - Chandana Roy; Pratiti Ghosh (Shahrekord University of Medical Sciences, 2023)
Introduction: Multidrug resistance (MDR) is primarily associated with reduced intracellular drug accumulation owing to overexpression of p-glycoprotein, an active efflux transporter. Competitive inhibition or allosteric modulation of p-glycoprotein may alter the pharmacokinetics of the drugs that serve as substrates, resulting in enhanced drug bioavailability and tissue penetration. This study endeavors to assess the efficacy of the components of reno-protective herbs in the inhibition of p-glycoprotein activity thereby enhancing the possibility of the retention of co-administered renal medications inside the target cells. Methods: Drug-likeness and pharmacokinetic properties were determined to ensure the safety and efficacy of herbal constituents. Molecular docking employing the CDOCKER module of Discovery Studio was performed to investigate the binding affinity between the active constituents and the p-glycoprotein receptor (6C0V). Molecular dynamics simulation was utilized to further assess the stability of the complex of receptors with the component bearing its maximal affinity. Results: The analyses suggested that the inhibitors viz., atisine, kutkin, and embelin from Aconitum heterophyllum, phylloquinone from Calendula officinalis, stigmasterol from Paederia foetida, and convallamarogenin from Convallaria majalis demonstrated maximum binding affinity towards p-glycoprotein. Conclusion: Atisine may thus be identified as the lead compound in the augmentation of drug bioavailability inside the cell, along with its reno-protective efficacy.